QUALITY MANAGEMENT OF FIQH LEARNING THROUGH THE IMPLEMENTATION OF THE 'PERFECT PRAYER WITH SANAD' STANDARD - Wahyu Syafa’at (Jurnal Ikhtibar Nusantara, 2026)
This research aims to analyze the quality management of Fiqh learning, which is an integral part of the Islamic Religious Education and Characteristics (PAI-BP) subject, through the implementation of the Perfect Prayer with Sanad standard at SMK Favorit Pungging Mojokerto. Quality management in vocational high schools faces significant challenges due to the limited time allocated for religious subjects. This study employs a qualitative descriptive method with a case study approach. Data collection was carried out through participant observation, interviews, and documentation. The results indicate that structured quality management—encompassing planning, intensive theoretical and demonstration-based implementation, and rigorous independent practical evaluation—is capable of significantly increasing students' worship accuracy. This implementation not only guarantees the quality of prayer movements in accordance with the Sunnah but also enhances the confidence of grade XII students as prospective alumni who are competent in leading worship within the community.